Skladenjska analiza slovenščine in slovenski jezikoslovno označeni korpusi - Ledinek, Nina (Jezik in slovstvo, 2018)
The article deals with the possibilities of using linguistically annotated corpora of Slovenian for syntactic analyses. Due to the inadequately developed Slovenian language infrastructure - at least eight syntactically annotated corpora of Slovenian are available to users, but due to their small size they only allow a limited scope of syntactic analysis - there is a small number of systematic and comprehensive corpus-based studies on Slovenian syntax, most of which rely on the analysis of morphosyntactically annotated corpora of Slovenian.
Keywords: drevesnica; korpusno jezikoslovje; oblikoskladenjsko označevanje korpusov; skladenjsko označevanje korpusov; skladnja; slovenščina